All-solid-state-supercapacitor and a process for the fabrication thereof - Kurungot, Sreekumar; Badiger, Manohar V.; Anothumakkool, Bihag; Torris, Arun (WO2014170912 A1, 2014)
The present invention discloses. all-solid-state supercapacitor (ASSP) with enhanced electrode-electrolyte interface which gives highest very high specific capacitance, areal capacitance and shows very low internal resistance (ESR). The invention particularly discloses the fabrication of all-solid-state supercapacitor by intercalation of solid state polymer electrolyte inside the conducting porous substrate coated with a charge storage electrode material to achieve the desired effect.